2013
DOI: 10.1007/s00167-013-2418-y
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation or reconstruction of PCL? A quantitative review

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 54 publications
1
20
1
Order By: Relevance
“…Considering the rate of normal (A)/nearly normal (B) IKDC outcomes as primary end point, a recent systematic review has reported an average success rate of 89.8% (SD 4.2) rate was after PCL augmentation, and 80.1% after reconstruction. Our IKDC outcomes are slightly lower to those reported by Del Buono et al 25 , but the follow up of the present study is longer, and almost all patients are athletes. Specifically, 16 patients (72.7%) returned to pre-injury sport activity level, and 3 (13.6%) returned to a lower level.…”
Section: Discussioncontrasting
confidence: 91%
“…Considering the rate of normal (A)/nearly normal (B) IKDC outcomes as primary end point, a recent systematic review has reported an average success rate of 89.8% (SD 4.2) rate was after PCL augmentation, and 80.1% after reconstruction. Our IKDC outcomes are slightly lower to those reported by Del Buono et al 25 , but the follow up of the present study is longer, and almost all patients are athletes. Specifically, 16 patients (72.7%) returned to pre-injury sport activity level, and 3 (13.6%) returned to a lower level.…”
Section: Discussioncontrasting
confidence: 91%
“…However, no differences have been demonstrated between remnant-preserving and conventional techniques. 38 …”
Section: Treatmentmentioning
confidence: 99%
“…This system is reliable and validated, and it has widely been used in the orthopaedic literature. [22][23][24][25][26][27] We point out that this is not a meta-analysis, but a descriptive quantitative review, and, according to the literature and relatively short-term available studies, it is not possible to draw definitive conclusions.…”
Section: Introductionmentioning
confidence: 98%